Web-Based Smart System for Mental Health Prediction to Educate the Community of Tangkahen Village in Supporting Healthy and Prosperous Living - Br Ginting, Dewi Sartika; Huzaifah, Ade Sarah; Ivanny Putri Marianto; Aurick Daffa Muhammad; Annisa Cahyani (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2025)
Mental health is crucial for individual well-being, enabling people to manage stress, work productively, and contribute to their communities. However, in Tangkahen Village, Namorambe District, Deliserdang Regency, mental health awareness remains low, with many villagers associating mental disorders with supernatural causes rather than seeking medical help. This community service project aims to address this gap by implementing a web-based smart system to predict mental health conditions and providing education on mental health issues. In collaboration with Angel Health Clinic, the project will include free health checks, socialization, and pre- and post-tests to evaluate the impact of the program on community knowledge. The goal is to promote healthier and more prosperous living through increased mental health awareness and early detection.